PEDAGOGIA DECOLONIAL EM INTERFACE COM OS ESTUDOS DO LETRAMENTO: DECOLONIZANDO MONUMENTOS HISTÓRICOS. - Effgen de Aguiar, André (Trabalhos em Lingüística Aplicada)
Our intention in this article is to think of a didactic proposal that intertwines theories such as decolonity (Mignolo, 2003, 2007; Quijano, 2005; Walsh, 2009, 2013, 2020), literacy studies (Street, 2003, 2014; Kleiman, 1995, 2006; Soares, 2003; Rojo, 2009), criticality (Aguiar, 2022; Freire, 1997, 2006; Carbonieri, 2016) and critical interculturality (Walsh, 2007, 2009, 2010), arriving at the constitution of the concept of Critical Digital Cartographic Literacy. The idea is that, through a decolonial pedagogy, these concepts converge and, in an organic way, the synthesis built from the dialogue of these theories can provide other possibilities of being, being, feeling, existing, doing, thinking, looking, listening and knowing (Walsh, 2013) at school through the production of virtual, interactive and decolonial maps.